2020
DOI: 10.1080/10903127.2020.1824049
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Prehospital Characteristics and Outcomes of Severe Traumatic Brain Injury in The Netherlands: The BRAIN-PROTECT Study

Abstract: A thorough understanding of the epidemiology, patient characteristics, trauma mechanisms, and current outcomes among patients with severe traumatic brain injury (TBI) is important as it may inform potential strategies to improve prehospital emergency care. The aim of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
14
4
Order By: Relevance
“…Data even suggest that prehospital TXA was often given in patients with TBI since patients who received prehospital TXA had higher AIShead, were more often prehospitally intubated and had higher PaCO2 with similar pH in ED (suggestive for prehospital hypoventilation) than patients who did not receive prehospital TXA. Several studies have reported various effects of TXA on outcome in TBI from depending on brain injury severity and timing of TXA administration [26] to no difference in outcome after prehospital TXA [27], or even a potential harmful effect of prehospital TXA on mortality in severe TBI patients [28]. The effect of TXA on TBI in this polytrauma population was beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Data even suggest that prehospital TXA was often given in patients with TBI since patients who received prehospital TXA had higher AIShead, were more often prehospitally intubated and had higher PaCO2 with similar pH in ED (suggestive for prehospital hypoventilation) than patients who did not receive prehospital TXA. Several studies have reported various effects of TXA on outcome in TBI from depending on brain injury severity and timing of TXA administration [26] to no difference in outcome after prehospital TXA [27], or even a potential harmful effect of prehospital TXA on mortality in severe TBI patients [28]. The effect of TXA on TBI in this polytrauma population was beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…After unadjusted logistic regression analyses, a multivariable model was built to account for potential confounders, including confounding by indication . Control variables were all simultaneously added to the model according to theoretical considerations and previous literature and included demographic factors (ie, age and sex), preinjury medical condition and medications (ie, American Society of Anesthesiologists Physical Status Classification System score and use of anticoagulant drugs), injury characteristics and severity (ie, trauma mechanism, Injury Severity Score [score range: 1-75, with the highest score indicating critical injury in at least 3 body regions or any unsurvivable injury], and initial GCS score [score range: 3-15, with the highest score indicating that the patient opens the eyes spontaneously, is oriented, and obeys commands]), operational characteristics (ie, involved HEMS provider and distance from the accident scene to the trauma center), and first recorded vital parameters at arrival of HEMS (ie, systolic blood pressure, heart rate, and oxygen saturation as measured by pulse oximetry). Numerical independent variables were modeled using restricted cubic splines to relax the assumption of a linear association between the variable and the logit of mortality.…”
Section: Methodsmentioning
confidence: 99%
“…17 Furthermore, in the Netherlands more than half of the TBI patients were involved in road traffic crashes. 18 The insights into the causes, patterns, and distributions of TBI patients from this study will be extremely helpful in policymaking, research, health management, and rehabilitation at the national level in our country and other developing nations. These methods provide promises for future studies to further clarify the true epidemiology of characteristics injury of brain trauma, which in turn will guide the development of clinical endpoints for diagnostic and the outcome of studies and data collection are of great importance in TBI studies, and is crucial to advance the care for TBI patients in the future.…”
Section: Discussionmentioning
confidence: 91%